Investigating Conviction, Erasure, and Salience Stories about a Gold Mining Project in Sangihe Island, Indonesia - Izzatun Nabila; Ribut Wahyudi (JEELS (Journal of English Education and Linguistics Studies), 2025)
Mining is one of the most significant contributors to environmental degradation. The media played their role in spreading the narrative about the situation on the ground. This narrative has the potential to affect readers' opinions toward the environment. Taking the gold mining operation on Sangihe Island cases, this article attempted to use Stibbe's (2015) story of “erasure, salience, and conviction” to analyze gold mining news by Tempo.co and VOI.id on the project of gold mining in Sangihe Island. The data were then examined with Stibbe's (2015) ecosophy as well as eco-critical discourse analysis. This article discovered that Tempo generated a valuable story for ecological wellbeing by building the conviction that 'mining causes ecological damage' and offering a clear image of the aspects of ecology in Sangihe. Meanwhile, the story from VOI.id developed a potentially detrimental effect by undermining the description of ecological features in Sangihe and building a conviction of economic benefit.